”Windows of Synchronization” and ”Non-chaotic Windows” - Lopes, Luís Mário (2015)
The dynamic of a chaotic dynamical system changes if we couple it together with another one. The changes depend on the dynamic of the systems and on the way the coupling is made. The strength of the coupling is controlled by the coupling strength constant. For some values of this constant synchronization may occur, defining a “window of synchronization”. We investigate the existence of this “window” for di↵erent dynamics and di↵erent couplings. We verify that other “windows” may occur. They are related to the fact that some couplings seem to confine drastically the chaotic behavior of the dynamical systems. We investigate one of these “windows”, the “fixed point non-chaotic window”, for the Symmetric Linear Coupling.